2021
DOI: 10.33963/kp.15985
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-related cardiac non-elective hospitalizations and pregnancy outcomes. A tertiary referral cardiac center experience

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-Non Commercial-No Derivatives 4.0 International License (CC BY-NC-ND 4.0), allowing third parties to download articles and share them with others, provided the original work is properly cited, not changed in any way, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…This group included four pregnancies with a mechanical mitral valve and one pregnancy with a mechanical tricuspid valve. It is well known that these prostheses, due to a low-velocity blood flow, are associated with high-risk thromboembolic complications in comparison to aortic prostheses, whatever anticoagulation regimen is used [7]. In the meta-analysis, Chan et al [4] reported 9.2% of MVT cases in pregnant women treated with sequential therapy.…”
Section: Thromboembolic Complicationsmentioning
confidence: 99%
“…This group included four pregnancies with a mechanical mitral valve and one pregnancy with a mechanical tricuspid valve. It is well known that these prostheses, due to a low-velocity blood flow, are associated with high-risk thromboembolic complications in comparison to aortic prostheses, whatever anticoagulation regimen is used [7]. In the meta-analysis, Chan et al [4] reported 9.2% of MVT cases in pregnant women treated with sequential therapy.…”
Section: Thromboembolic Complicationsmentioning
confidence: 99%
“…The prevalence of hypertension-related disorders in pregnancy remains a significant clinical problem that contributes to an increase in maternal morbidity and mortality and influences the risk of future cardiovascular complications [1]. It is recommended to monitor blood pressure (BP) during pregnancy using office BP measurements (OBPM) with the support of outpatient measurements, which include home BP (HBPM) and ambulatory BP measurements (ABPM) [2].…”
Section: Introductionmentioning
confidence: 99%